Engineering Secure Internet of Things Systems - Aziz, Benjamin (IET security series ;, 2016)
The Internet of Things (IoT) - the emerging global interconnection of billions of 'smart' devices - will be collecting increasing amounts of private and sensitive data about our lives, and will require increasing degrees of reliability and trustworthiness in terms of the levels of assurance provided with respect to confidentiality, integrity and availability. This book examines these important security considerations for the IoT Topics covered include a security survey of middleware for the IoT; privacy in the IoT; privacy and consumer IoT - a sensemaking perspective; a secure platform for smart cities and IoT; model-based security engineering for the IoT; federated identity and access management in IoT systems; the security of the MQTT protocol; securing communications among severely constrained, wireless embedded devices; lightweight cryptographic identity solutions for the IoT; and a reputation model for the IoT.